Rivalry and Forbearance in the European Airline Industry: Evidence of an Inverted U-Shaped Competitive Pattern - Ghertman, Michel; Guedri, Zied (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2012)
This study develops and tests a theoretical framework which suggests that the relationship between the level of multi-territory (or multi-point) contact and rivalry takes the form of an inverted U-shaped relationship. Drawing on a large sample of European airlines over the period 2001-2006, we provide empirical support for the inverted U-shaped relationship between multi-territory contact and rivalry as reflected by entries into and exits from the territory of a competitor. We conclude that competition between firms exhibits successive periods of rivalry and forbearance, possibly independently of time and institutional settings.